1997
DOI: 10.1111/j.1432-1033.1997.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Cathepsin S by its Propeptide — Specificity and Mechanism of Action

Abstract: The interaction of human recombinant full-length cathepsin S propeptide (amino acids 16-114) with mature cysteine proteinases was studied with respect to selectivity and pH dependence. The inhibitory capacity was tested towards mature human recombinant cathepsin S, purified cathepsin L from rat and Paramecium tetraurelia, rat cathepsin B, human cathepsin H, and papain. The propeptide of cathepsin S strongly inhibited cathepsin S (Ki = 0.27 nM) and the two cathepsin L species (Ki = 0.36 nM) at neutral pH. Papai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
64
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(74 citation statements)
references
References 25 publications
(16 reference statements)
8
64
0
Order By: Relevance
“…Cathepsins-Cathepsin B was purified from rat liver (13), cathepsin H from Epstein-Barr virus transformed human B-lymphocytes (14), and cathepsin L from the culture medium of non-small cell lung cancer cell line EPLC 32 M1 (15). All cathepsins were purified to homogeneity, and the concentration of the cathepsins was determined by titration with E64 (16).…”
Section: Methodsmentioning
confidence: 99%
“…Cathepsins-Cathepsin B was purified from rat liver (13), cathepsin H from Epstein-Barr virus transformed human B-lymphocytes (14), and cathepsin L from the culture medium of non-small cell lung cancer cell line EPLC 32 M1 (15). All cathepsins were purified to homogeneity, and the concentration of the cathepsins was determined by titration with E64 (16).…”
Section: Methodsmentioning
confidence: 99%
“…21 For the cathepsin L propeptide, lack of inhibition has been associated with partial unfolding of the propeptide and formation of a molten globule state under acidic conditions. 25 Moreover, under these conditions, it has been demonstrated that the cathepsin S propeptide is slowly degraded by mature cathepsin L. 21 To date, the interaction between mature Der p 1 and its propeptide has not been investigated due to the difficulty of obtaining correctly matured recombinant Der p 1 (rDer p 1). In order to characterize this interaction, we studied the activation steps involved in the zymogen maturation mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24] Some cathepsin propeptides have been shown to display a strong inhibition capacity at neutral pH, with values of the dissociation constant K D ranging from 0.12 nM for cathepsins L and B to 7.6 nM for cathepsins S and K. Interactions between the propeptides and the proteases are pH dependent: At neutral pH, slow binding interactions occur, whereas at acidic pH, weak or no interactions are observed. 21 For the cathepsin L propeptide, lack of inhibition has been associated with partial unfolding of the propeptide and formation of a molten globule state under acidic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NH 2 -terminal propeptide domain of the cathepsin L -like proteases is an inhibitor of the active enzyme in its latent form, which is then removed on its activation (7,8). Using purified proteases in peptidolytic assays, the ability of the propeptide to act as reversible inhibitors of their cognate protease has been shown (9,10).…”
Section: Introductionmentioning
confidence: 99%